Family Response to Changes in Family Key Functions Due to Covid–19 in Hukurila, Ambon City - Feky Manuputty; Prapti Murwani; Simona Christina Henderika Litaay; Rizki Muhammad Ramdhan (Budapest International Research and Critics University, 2022)
Pandemic COVID-19 affects huge family roles and functions. This has resulted in a drastic decline in the family economy, limitations in socializing and interacting directly with the people around them, and the educational paradigm. Not only globally but also to the people of the land of Hukurila, The Southern Leitimur District, and The City of Ambon. For that purpose, the research aims to know and explain the family's response to the fundamental change in family function brought about by the COVID-19 pandemic in the land of Hukurila. Fifteen people were accounted for the informants in this study and were selected using purposive sampling. The data source was used through interviews and observations. The study found a significant change in the five functions of the family, as well as how the family responded to the change in the new custom of the COVID-19 pandemic.